2017
DOI: 10.14295/cs.v8i1.1546
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest quality of ‘Roxo de Valinhos’ fig fruits grown in semi-arid conditions

Abstract: Aiming to evaluate the postharvest quality of ‘Roxo de Valinhos’ fig fruits grown in semi-arid conditions, this experiment was carried out in November, 2014, where fig fruit variety ‘Roxo de Valinhos’ were harvested from plants located at the didactic orchard of the Federal Rural University of Semi-Arid (UFERSA), Mossoró-RN, Brazil. Fruits were randomly harvested from 30 fig plants, spaced 2 m x 1.5 m, with 2 years old, according to three the fruit development stages (50%, 75% and 100% mature). The fruits were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The pH remained within 5.19 and 5.45 for the fruits of the first cycle, and within 5.32 and 5.42 for those of the second cycle, with a significant difference occurring between stages and pruning times only for the green figs (Table 3). These values were above those of the studies by Freitas et al (2015) and Silva et al (2017a). The pH is an important attribute for the industrialization of the pulp since the lower is its value, the higher the antimicrobial effect and the guarantee of conservation (Caetano et al, 2017).…”
Section: Resultsmentioning
confidence: 54%
“…The pH remained within 5.19 and 5.45 for the fruits of the first cycle, and within 5.32 and 5.42 for those of the second cycle, with a significant difference occurring between stages and pruning times only for the green figs (Table 3). These values were above those of the studies by Freitas et al (2015) and Silva et al (2017a). The pH is an important attribute for the industrialization of the pulp since the lower is its value, the higher the antimicrobial effect and the guarantee of conservation (Caetano et al, 2017).…”
Section: Resultsmentioning
confidence: 54%
“…Additionally, few studies have been carried out with exotic species in semiarid regions. Silva et al (2017) found that figs from the 'Roxo de Valinhos' cultivar showed high quality under semiarid conditions.…”
Section: Introductionmentioning
confidence: 98%